2014
DOI: 10.4028/www.scientific.net/amr.995.49
|View full text |Cite
|
Sign up to set email alerts
|

Weeds as Alternative Useful Medicinal Source: <i>Mimosa pudica</i> Linn. on Diabetes Mellitus and its Complications

Abstract: Diabetes mellitus is one of the major reasons for mortality worldwide and numerous scientific studies are going on to find plausible solutions to overcome and manage diabetes and its related infirmities. Traditional medicines use medicinal plants as anti-diabetic agents and despite being a disturbing weed to farming landMimosa pudicaLinn. has a high traditional usage for various purposes including anti-diabetic complications. The objective of this article is to accumulate and organise literatures based on trad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 28 publications
0
7
0
1
Order By: Relevance
“…The extract and its fractions also showed free radical‐scavenging activity as determined by 1,1‐diphenyl‐2‐picrylhydrazyl‐hydrate (DPPH), total flavonoid content, and total phenolic content assays. The study revealed that M. pudica is a potential candidate to treat diabetes (Tunna and others , 2015).…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…The extract and its fractions also showed free radical‐scavenging activity as determined by 1,1‐diphenyl‐2‐picrylhydrazyl‐hydrate (DPPH), total flavonoid content, and total phenolic content assays. The study revealed that M. pudica is a potential candidate to treat diabetes (Tunna and others , 2015).…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…Pemanfaatan: Puteri malu ditanam sebagai tanaman penutup tanah di perkebunan kelapa dan pakan sapi (Soerjani et al, 1987). Selain itu, bagian akarnya juga dimanfaatkan sebagai obat diabetes oleh masyarakat di Bangladesh, India, Thailand, dan Filipina (Tunna et al, 2014).…”
Section: Anak Suku Mimosoideaeunclassified
“…Some of the major chemical constituents of this species are chebulagic acid, chebulic acid, corilagin, phyllanemblinin A, gallic acid, ellagic acid, malic acid, mucic acid, (-)epicatechin, and mallonin [ 15 ]. M. pudica of the family Fabaceae commonly found in South Asian countries possesses antidiabetic, antibacterial, wound-healing, antivenom, and anticancer properties and is traditionally used for treatment of fever and dyspepsia [ 16 ]. Phytochemical analysis revealed the presence of flavonoids C-glycosides, sterols, terpenoids, tannins, fatty acids, p-coumaric acid, mimopudine, and mimosine in M. pudica [ 17 ].…”
Section: Introductionmentioning
confidence: 99%